Acute hospital admissions among nursing home residents: a population-based observational study - Jamtvedt Gro; Riise Trond; Graverholt Birgitte; Ranhoff Anette H; Krüger Kjell; Nortvedt Monica W (BMC, 2011)
Abstract Background Nursing home residents are prone to acute illness due to their high age, underlying illnesses and immobility. We examined the incidence of acute hospital admissions among nursing home residents versus the age-matched community dwelling population in a geographically defined area during a two years period. The hospital stays of the nursing home population are described according to diagnosis, length of stay and mortality. Similar studies have previously not been reported in Scandinavia. Methods The acute hospitalisations of the nursing home residents were identified through ambulance records. These were linked to hospital patient records for inclusion of demographics, diagnosis at discharge, length of stay and mortality. Incidence of hospitalisation was calculated based on patient-time at risk. Results The annual hospital admission incidence was 0.62 admissions per person-year among the nursing home residents and 0.26 among the community dwellers. In the nursing home population we found that dominant diagnoses were respiratory diseases, falls-related and circulatory diseases, accounting for 55% of the cases. The median length of stay was 3 days (interquartile range = 4). The in-hospital mortality rate was 16% and 30 day mortality after discharge 30%. Conclusion Acute hospital admission rate among nursing home residents was high in this Scandinavian setting. The pattern of diagnoses causing the admissions appears to be consistent with previous research. The in-hospital and 30 day mortality rates are high.